A novel approach for time-dependent axial soil resistance in the analysis of subsea pipelines. (September 2015) - Carneiro, D.; White, D.J.; Danziger, F.A.B.; Ellwanger, G.B.
Abstract: A novel approach for modelling axial pipe–soil interaction, consisting of bespoke finite elements, is proposed. The purpose is to have a model that represents a two-dimensional slice of soil perpendicular to the pipe which is computationally cheap enough to be incorporated in global analysis of subsea pipelines, whilst capable of capturing detailed time-dependent soil response, which involves partial drainage and cyclic plasticity. This is achieved by handling the circumferential dimension analytically, reducing the behaviour of the two-dimensional soil slice to a one-dimensional case. Coupled consolidation analysis along a vertical sequence of one-dimensional elements beneath each pipeline node, tailored to represent the axial–vertical (or -radial) plane across the seabed semi-space, is supplemented by an analytical solution for the circumferential drainage. The paper presents the model development, its implementation through symbolic programming and validation against previously published continuum finite element analysis results.